Pemikiran Pendidikan Sidiq Amien Dalam Perspektif Pendidikan Islam Pada Persatuan Islam (Persis): Integrasi Ilmu Agama Dan Ilmu Umum Sebagai Konsep Pendidikan Kontemporer - Iki Supriadi (Halaqa: Journal of Islamic Education, 2026)
This study aims to examine the educational thoughts of  Sidiq Amien in the context of Islamic education in Indonesia, particularly as implemented within the Persatuan Islam (PERSIS) organization. This research is important due to the relevance of his ideas in addressing the challenges of globalization and secularization in Islamic education. The main objective of this study is to analyze how  Sidiq Amien’s educational concepts, which integrate religious and general sciences, can contribute to the contemporary Islamic education system. The research methodology used is a qualitative approach with an interpretive research design and hermeneutic analysis, aimed at uncovering the meaning and context behind Amien's educational ideas. The results show that  Sidiq Amien's educational thought is firmly grounded in Islamic values, including the strengthening of morals and the integration of knowledge in education. The novelty of this study lies in its effort to connect his ideas with the current challenges in Islamic education and offer a new perspective on the importance of integrating religious and general sciences. The implications of this research are to strengthen the Islamic education system based on values of tawhid, ethics, and intellectual capacity in responding to the development of the times.